APPLICATION OF THE PROBLEM-SOLVING LEARNING MODEL TO IMPROVE LEARNING OUTCOMES IN IPAS LEARNING IN GRADE IV STUDENTSSD N MATARAM - Jecelind Cheril Talitha Rahma (CV Grasta Glory, 2025)
This research aims to improve student learning outcomes in science subjects through the application of the problem-solving learning model in grade IV of SDN Mataram. The main problem in this study is explicitly formulated as: